Instrument Department at Dow plant in Midland, Michigan - Dow Chemical Company (1948)
General view of the Instrument Department workroom at the Dow Chemical Company plant located in Midland, Michigan. Established in 1926, the Instrument Department was responsible for the installation and maintenance of the assorted apparatus necessary to manage the plant's production facilities and processes. The department notably maintained accurate standards for temperatures, voltage, resistance, flow and pressures against which the plant's instruments were regularly calibrated and checked for accuracy.
Keywords: Machine parts--Maintenance and repair; Industries; Scientific apparatus and instruments; Machine parts--Standards; Scientific apparatus and instruments--Calibration; Calibration; Machine parts--Testing; Machine parts; Employees; Dow Chemical Company